2019
DOI: 10.1016/j.nicl.2019.101875
|View full text |Cite
|
Sign up to set email alerts
|

Structural anomaly in the reticular formation in narcolepsy type 1, suggesting lower levels of neuromelanin

Abstract: The aim of this study was to investigate structural changes in the brain stem of adolescents with narcolepsy, a disorder characterized by excessive daytime sleepiness, fragmented night-time sleep, and cataplexy. For this purpose, we used quantitative magnetic resonance imaging to obtain R1 and R2 relaxation rates, proton density, and myelin maps in adolescents with narcolepsy ( n = 14) and healthy controls ( n = 14). We also acquired resting state functional magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Additionally, others have reported alterations of several DWI parameters (e.g., increased mean diffusivity values without fractional anisotropy changes) in the ventral tegmental area and the dorsal raphe nuclei of patients with narcolepsy-cataplexy (Scherfler and others 2012). A recent study by Drissi and others (2019) found signs of lower levels of neuromelanin in the rostral reticular formation of the brainstem. Altogether, wide ranging functional and structural neuroimaging techniques have provided complimentary data to suggest functional and anatomical changes of the brainstem may underlie the symptoms of narcolepsy.…”
Section: Clinical Features and Pathogenesis Of Narcolepsymentioning
confidence: 92%
“…Additionally, others have reported alterations of several DWI parameters (e.g., increased mean diffusivity values without fractional anisotropy changes) in the ventral tegmental area and the dorsal raphe nuclei of patients with narcolepsy-cataplexy (Scherfler and others 2012). A recent study by Drissi and others (2019) found signs of lower levels of neuromelanin in the rostral reticular formation of the brainstem. Altogether, wide ranging functional and structural neuroimaging techniques have provided complimentary data to suggest functional and anatomical changes of the brainstem may underlie the symptoms of narcolepsy.…”
Section: Clinical Features and Pathogenesis Of Narcolepsymentioning
confidence: 92%
“…Our present cardiac- and very low frequency -related results partly overlap with an earlier task- and resting-state imaging findings in patients with narcolepsy. In two studies, Drissi et al found that in patients with narcolepsy the dynamic resting activity of the DMN is unstable and that a lower R2 relaxation rate in the brainstem’s rostral reticular formation may indicate lower neuromelanin levels in the LC in narcolepsy when compared to the healthy population 11 , 15 . Moreover, in narcolepsy increased deactivation of the DMN has been observed under cognitive burden induced by a working memory test suggesting dysregulation of sustained attention by an imbalance in the utilization of cognitive resources 14 .…”
Section: Discussionmentioning
confidence: 99%
“…These AAN innervations participate in the control of autonomic functions and arousal/sleep via their respective neurotransmitters in dense innervations to the hypothalamus, thalamus, basal ganglia, and neocortex 9 . Earlier imaging studies in narcolepsy have shown structural alterations in cortical and subcortical brain regions including the limbic system and brainstem along its nuclei e.g., LC and neocortex 10 , 11 . Research conducted with task-fMRI have found altered activation of the amygdala, a part of the limbic system, in tasks with humor/reward paradigms along with increased deactivation of the default mode network (DMN) under cognitive burden in narcolepsy 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…59 Blystad et al 63 investigated the use of T 1 , T 2 , and PD obtained by the MDME method to identify active MS plaques without GBCA administration. Beyond MS, quantitative values from the MDME were used to show R2 differences associated with low concentrations of neuromelanin in the rostral reticular formation near the superior cerebellar peduncle in narcolepsy 64 ; to assess the degree of myelination in preterm neonates 65 and SWS 66 ; and to measure T 1 shortening in the globus pallidus related to multiple exposures to macrocyclic GBCA, specifically gadobutrol. 67 Quantitative maps obtained from MRF were used to diagnose hippocampal sclerosis (HS) in patients with mesial temporal lobe epilepsy (MTLE).…”
Section: Clinical Utility and Applicationsmentioning
confidence: 99%